1442The burden of COVID-19 in Australia in 2020. (2nd September 2021) - Moon, Lynelle; Reynolds, Anna; Gourley, Michelle
Abstract: Background: During 2020, there were nearly 28, 500 cases of COVID-19 in Australia. Burden of disease estimates for COVID-19 have not been calculated for the Australian population. Burden of disease data on COVID-19 provide valuable information on the impact of the disease, including both fatal and non-fatal effects. Methods: Burden of disease is measured using the summary measure disability-adjusted life years (DALYs). One DALY is 1 year of 'healthy life' lost due to illness (Years Lived with Disability) and/or death (Years of Life Lost)—the more DALYs associated with a disease or injury, the greater the burden. The analysis draws on Australian deaths, incidence and severity, as well as methods and other inputs developed in other countries reflecting current understanding about this new disease. Results: There were over 8, 300 DALYs lost due to COVID-19 in 2020 in Australia; 97% of the disease burden arose from fatal cases. Males lost an average of 10.7 years, and females 8.1 years, due to dying from COVID-19, using an aspirational life expectancy. The burden of disease estimates for Australia for COVID-19 are much lower than the leading diseases causing burden. Conclusions: The relatively low burden for COVID-19 in Australia in 2020 compared to other diseases and other countries reflects the success Australia had in containing the virus. Key messages: Most of the burden due to COVID-19 in Australia was fatal. Burden of disease estimates for COVID-19 in Australia for 2020 are much lower than the leading diseases.